PENGARUH UKURAN PERUSAHAAN, LABA PERUSAHAAN, SOLVABILITAS, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2015-2017) - Nada Lisdara; Roni Budianto; Roza Mulyadi (Jurnal Riset Akuntansi Terpadu, 2019)
This study aims to prove the factors that affect audit report lag. Factors tested in this study is a company size, company profit, solvency, and cpa firm size on audit report lag. This study uses secondary data with a total sample of 46 food and beverages companies listed in Indoesia Stock Exchange in the year 2015 to 2017 by using saturation sampling method. The statistical method used in this study were multiple linear regression at a significance level of 5% with test equipment program computer SPSS version 23. These results indicate that the company size, company profit, and cpa firm size negative effect on audit report lag and solvency has no significant effect on audit report lag.